2005
DOI: 10.1152/ajpregu.00693.2004
|View full text |Cite
|
Sign up to set email alerts
|

Green tea extract improves endurance capacity and increases muscle lipid oxidation in mice

Abstract: Green tea contains a high level of polyphenolic compounds known as catechins. We investigated the effects of green tea extract (GTE), which is rich in catechins, on endurance capacity, energy metabolism, and fat oxidation in BALB/c mice over a 10-wk period. Swimming times to exhaustion for mice fed 0.2-0.5% (wt/wt) GTE were prolonged by 8-24%. The effects were dose dependent and accompanied by lower respiratory quotients and higher rates of fat oxidation as determined by indirect calorimetry. In addition, feed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
152
0
4

Year Published

2005
2005
2019
2019

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 172 publications
(161 citation statements)
references
References 46 publications
5
152
0
4
Order By: Relevance
“…EGCG can modulate insulin secretion and insulin sensitivity (16,17). EGCG has also been shown in skeletal muscle to promote fatty acid oxidation (18). Furthermore, EGCG has been suggested to reduce blood pressure through enhancing vascular endothelial function and insulin sensitivity (19).…”
Section: Epigallocatechin-3-gallate (Egcg)mentioning
confidence: 99%
“…EGCG can modulate insulin secretion and insulin sensitivity (16,17). EGCG has also been shown in skeletal muscle to promote fatty acid oxidation (18). Furthermore, EGCG has been suggested to reduce blood pressure through enhancing vascular endothelial function and insulin sensitivity (19).…”
Section: Epigallocatechin-3-gallate (Egcg)mentioning
confidence: 99%
“…[21][22][23] Briefly, we used an acrylic pool (length  width  depth: 90  45  45 cm 3 ) filled with water to a depth of 38 cm. The current in the pool was generated by a pump (type C-P60H; Hitachi, Tokyo, Japan), and the strength was adjusted using a valve.…”
Section: Swimming Exmentioning
confidence: 99%
“…23 Hence, repeated exposure to increased plasma fatty acids during Ex might produce adaptive changes that stimulate lipid catabolism. Catecholamines released from sympathetic nerves promote lipid mobilization and thermogenesis via b3-adrenoreceptors.…”
Section: Obesity Suppression and Tea Catechins T Murase Et Almentioning
confidence: 99%
“…28) In addition, Murase et al reported that green tea extract, which contains high levels of polyphenolic compounds, increased fatty acid beta-oxidation in the liver and muscles of mice. 29,30) Li et al also showed that green tea leaf extract enhanced hepatic expression of lipolytic transcriptional factor PPAR-alpha and improved lipid homeostasis in a fructose-fed insulin-resistant hamster model. 31) In addition, previous reports have indicated that BBL contains a variety of phenolic compounds, such as chlorogenic acid, quercetin, caffeic acid, and procyanidins, and has oxygen radical absorbance capacity and antileukaemic activity.…”
mentioning
confidence: 98%